2022
DOI: 10.3389/fpls.2022.999793
|View full text |Cite
|
Sign up to set email alerts
|

Large plants enhance aboveground biomass in arid natural forest and plantation along differential abiotic and biotic conditions

Abstract: Big-sized trees, species diversity, and stand density affect aboveground biomass in natural tropical and temperate forests. However, these relationships are unclear in arid natural forests and plantations. Here, we hypothesized that large plants (a latent variable of tall-stature and big-crown, which indicated the effect of big-sized trees on ecosystem function and structure) enhance aboveground biomass in both arid natural forests and plantations along the gradients of climate water availability and soil fert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 71 publications
1
0
0
Order By: Relevance
“…Previously, studies based on 73 plots ranging from 25 to 400 m 2 in the arid northwestern region have demonstrated that the upper 20% of large vegetation contributes to an impressive 59.25% of the total plot AGB [25]. This outcome is corroborated by the findings of this research.…”
Section: Significance Of Large Trees In Arid Mountains' Forestssupporting
confidence: 89%
See 2 more Smart Citations
“…Previously, studies based on 73 plots ranging from 25 to 400 m 2 in the arid northwestern region have demonstrated that the upper 20% of large vegetation contributes to an impressive 59.25% of the total plot AGB [25]. This outcome is corroborated by the findings of this research.…”
Section: Significance Of Large Trees In Arid Mountains' Forestssupporting
confidence: 89%
“…In the arid region of Northwestern China, a recent study utilized structural equation models to investigate the influence of the top 20% of large trees on AGB in both natural and artificial forests. The findings underscore the substantial contribution of large trees to forest biomass, underscoring their significance in arid region ecosystems [25]. Nevertheless, there is currently no established prediction model for AGB specific to large trees in arid regions.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Particularly in even-aged stands that regenerated after fire, since the relationship between competition and habitat conditions are more complicated, the association of TD and AGB might be affected by insect outbreak or windthrow [68]. TD significantly affected AGB in temperate forest, consistent with the findings of Yang et al [69]; meanwhile, an allometric relationship of TD and AGB was found within this biome. Most likely, community type and species diversity should be considered, such as in broadleaf and conifer forests or mixed forests [70], since trees' biological traits (e.g., leaf area, thickness) may regulate different nutrient uptake and partitioning.…”
Section: Differences Between Stand Structural Characteristics In Term...supporting
confidence: 87%